Study of Dislocations in Homoepitaxially and Heteroepitaxially Grown AlN Layers. Issue 24 (2nd November 2020) - Goto, Ken; Takekawa, Nao; Nagashima, Toru; Yamamoto, Reo; Pozina, Galia; Dalmau, Rafael; Schlesser, Raoul; Collazo, Ramón; Monemar, Bo; Sitar, Zlatko; Boćkowski, Michał; Kumagai, Yoshinao
Abstract : Dislocation densities in AlN layers grown on c ‐plane sapphire and physical vapor transport‐grown AlN (PVT‐AlN) (0001) substrates, by metalorganic vapor phase epitaxy (MOVPE) and hydride vapor phase epitaxy (HVPE), respectively, are evaluated from the density of etch pits formed in sodium hydroxide (NaOH)/potassium hydroxide (KOH) eutectic heated to 450 °C. In the heteroepitaxial layers grown by MOVPE on the sapphire substrates, etch pits with different sizes are formed. Cross‐sectional transmission electron microscopy (TEM) observations reveal that the large, medium, and small pits, with densities of 1.4 × 10 6, 2.6 × 10 7, and 6.9 × 10 9 cm −2, respectively, correspond to screw, mixed, and edge dislocations, respectively. In contrast, in the homoepitaxial layers grown by HVPE on the PVT‐AlN substrates, only one kind of etch pit with uniform size corresponding to the edge dislocations is formed with a density of 10 3 –10 4 cm −2 . Cross‐sectional TEM observation confirms that the edge dislocations in the homoepitaxial layer propagate from the substrate through the interface, which indicates that the dislocation density does not increase during homoepitaxial growth by HVPE. The HVPE‐AlN homoepitaxial layers grown on the PVT‐AlN substrates are found to have very low dislocation density. Abstract : The types and their densities of the dislocations in heteroepitaxially and homoepitaxially grown AlN layers are investigated by the formation of etch pits by wet chemical etching. With this method, it is possible to accurately evaluate the dislocation density of high‐quality AlN layers (dislocation density < 10 4 cm −2 ), which is difficult to evaluate by conventional methods.